Catharine Parr Traill's The female emigrant's guide : cooking with a Canadian classic - Cooke, Nathalie; Lucas, Fiona (Carleton library series, 2017)
"What did you eat for dinner today? Did you make your own cheese? Butcher your own pig? Collect your own eggs? Drink your own home-brewed beer? Shanty bread leavened with hops-yeast, venison and wild rice stew, gingerbread cake with maple sauce, and dandelion coffee - this was an ordinary backwoods meal in Victorian-era Canada. Originally published in 1855, Catharine Parr Traill's classic Female Emigrant's Guide, with its admirable recipes, candid advice, and astute observations of local food sourcing, offers an intimate glimpse into the daily domestic and seasonal routines of settler life. This toolkit for historical cookery, redesigned and annotated in an edition for use in contemporary kitchens, provides readers with the resources to actively use and experiment with recipes from the original Guide. Containing modernized recipes, a measurement conversion chart, and an extensive glossary, this volume also includes discussions of cooking conventions, terms, techniques, and ingredients that contextualize the social attitudes, expectations, and challenges of Traill's world and the emigrant experience. In a distinctive and witty voice expressing her can-do attitude, Catharine Parr Traill's Female Emigrant's Guide unlocks a wealth of information on historical foodways and culinary exploration, now in a format for the twenty-first century."--